2014
DOI: 10.1590/0104-6632.20140313s00003014
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial analysis of films processed from chitosan and N,N,N-trimethylchitosan

Abstract: -Chitosan and its derivatives have been proposed as bactericidal and fungicidal agents against a large numbers of gram-negative and gram-positive bacteria and fungi. Some antimicrobial mechanisms have been proposed for chitosan, with the most widely acceptable being the presence of charged-NH 3 + groups in the polymer backbone and its interactions with the bacterial wall constituents. Since this mechanism is based on an electrostatic interaction, it suggests that the greater the number of cationic amines, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 33 publications
(32 reference statements)
0
8
0
1
Order By: Relevance
“…Since these samples were neutralised before testing for antibacterial, the presented low values may well be related to incorporated tannic acid, compared to acetic acid which is reported to have higher antibacterial effect for these bacteria even at lower concentrations [55,56]. Even though chitosan has been reported to have antibacterial effect [57], the values found in this work for samples containing cellulose with chitosan had a weak antibacterial activity. When they were incorporated with tannic acid, the antibacterial effect is still lower than when compared to samples without chitosan.…”
Section: Antibacterial Activitymentioning
confidence: 62%
“…Since these samples were neutralised before testing for antibacterial, the presented low values may well be related to incorporated tannic acid, compared to acetic acid which is reported to have higher antibacterial effect for these bacteria even at lower concentrations [55,56]. Even though chitosan has been reported to have antibacterial effect [57], the values found in this work for samples containing cellulose with chitosan had a weak antibacterial activity. When they were incorporated with tannic acid, the antibacterial effect is still lower than when compared to samples without chitosan.…”
Section: Antibacterial Activitymentioning
confidence: 62%
“…Moreover, all antibacterial activities of low MM chitosan with the DDA of 90.58% were higher than that of high MM with the DDA of 52.14%. A previous study showed that the DDA as well as MM greatly affected the antibacterial activity, and chitosan with higher DDA values showed better antimicrobial activity (Goy & Assis, ).…”
Section: Resultsmentioning
confidence: 99%
“…There are some hypotheses about the antimicrobial mechanism of chitosan. The ionic interactions between positive charges of amino groups and negative bacteria surface molecules in acid conditions alter the membrane permeability leading to cellular lysis [ 40 , 47 ]. Another mechanism could be the interaction with essential nutrients for bacteria [ 48 ].…”
Section: Discussionmentioning
confidence: 99%